Strength and Deformation of Carbonaceous Shale Fillers Subjected to Water Content Fluctuation - Yafei Huang; Junyong Liu; Qian Wu; Lihua Yin; Xuesong Mao; Weipeng Ge (Advances in Civil Engineering)
Carbonaceous shale is a dark, soft rock with poor water stability. To evaluate the feasibility of using this rock as a filler material for highway embankments, the scanning electron microscopy (SEM) test, the particle size analysis before and after vibration compaction, the California bearing ratio (CBR) test of repeated dry–wet alternation, the compression tests with different moisture, and the resilience modulus test of in-site infiltration were conducted. The test results indicated that the higher weathering degree of carbonaceous shale usually goes with the looser structure and the higher content of hydrophilic clay. The larger particle size in the filler has a higher crushing ratio. The CBR value of the filler exhibited a rapid decay and then gradually stabilized with the increase of the time of dry–wet alternation. The compression deformation and particle breakage ratio of the filler material with saturated water content significantly increased compared to the optimal water content. After being infiltrated by water, the resilience modulus of the top surface of the carbonaceous shale filler decreased significantly. According to the research, although moisture content changes and dry–wet alternation have a significant impact on the strength and deformation performance of carbonaceous shale, it can be used as embankment filling material under the premise of taking engineering measures such as setting waterproof layers, restricting usage positions, and eliminating disintegration in advance. The research results can guide the design and construction of embankments using carbonaceous shale as filling material.